A metal ion-drug-induced self-assembly nanosystems for augmented chemodynamic and chemotherapy synergetic anticancer therapy. (March 2022) - Zhao, Dong-Hui; Li, Chao-Qing; Hou, Xiao-Lin; Wu, Gui-Ying; Xie, Xiao-Ting; Zhu, Dan; Jin, Fang; Zhao, Yuan-Di; Liu, Bo
Abstract: The complexities in the integration of carrier materials and functional materials make it challenging to promote nanoprobes for clinical translation. Carrier-free self-assembled nanosystems have been proposed as a promising strategy for synergetic anticancer therapy. In this study, carbon dots, copper ions, and doxorubicin (DOX) were assembled into nanoparticles (CCD) to achieve augmented chemodynamic therapy (CDT). The assembled CCD NPs were biodegradable and responsive to GSH and acidic pH in the tumor microenvironment resulting in the release of the DOX, Cu 2+, and carbon dots. The intracellular H2 O2 level was elevated by DOX activated the nicotinamide adenine dinucleotide phosphate oxidases. The GSH was depleted by Cu 2+, and the generated Cu + as well as peroxidase-like carbon dots could catalyze the intracellular H2 O2 to produce cytotoxic ·OH to achieve enhanced CDT effects. Chemotherapy effects were enhanced through increasing drug sensitivity and inhibiting drug efflux after the intracellular redox balance was broken by CCD NPs. The in vivo experiments revealed that CCD NPs possessed the excellent biocompatibility and synergistic anti-tumor ability, which could completely inhibit the growth of 4T1 tumors. As a novel carrier-free nanoprobes, CCD NPs with responsiveness to the tumor microenvironment may have great potential in cancer chemodynamic therapy with high specificity. Graphical abstract: Image 1